2020
DOI: 10.1111/joor.12881
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of DMP1 maintains cranial sutures in mice

Abstract: Cranial Suture, a fibrocellular structure in which two osteogenic fronts interact with each other, accounts for most of the bone growth of the face and calvaria. 1 As bone growth sites, suture permits the movement of craniofacial bones, allowing expansion of the brain case and extension of the craniofacial complex. 2 Also, as fibrous joint, cranial suture is capable to absorb outer mechanical forces to protect brain. 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The junctures between the bones of the skull where the bones are held tightly together by fibrous tissue are called sutures. It has been reported that sutures are important for calvarial bone development and maintenance [ 31 ]. Approximately 85.5 ± 1.1% of the cells in the sutures possessed ARL13B-mCherry+ primary cilia, and the ciliary length varied from 5 to 7 μm ( Figure 5 H) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The junctures between the bones of the skull where the bones are held tightly together by fibrous tissue are called sutures. It has been reported that sutures are important for calvarial bone development and maintenance [ 31 ]. Approximately 85.5 ± 1.1% of the cells in the sutures possessed ARL13B-mCherry+ primary cilia, and the ciliary length varied from 5 to 7 μm ( Figure 5 H) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thinner cortical bone, decreased trabecular number and diminished osteocyte lacuna were detected in the S89G-DMP1 mice [11]. Interestingly, craniomaxillofacial deformities and cranial structure abnormalities were also clearly observed [16]. Additionally, our previous studies showed that DMP1-PG was highly expressed in the cartilage callus of fracture sites, and the S89G-DMP1 mouse fracture endochondral ossification model displayed abnormal chondrogenesis and delayed fracture healing.…”
Section: Introductionmentioning
confidence: 83%
“…DMP1-PG is a novel acidic ECM PG that is highly expressed in the bone matrix, cartilage and fracture callus. DMP1-PG deficiency could lead to abnormal craniomaxillofacial development and delayed fracture healing in long bones [16]. However, we still have limited knowledge about the special role of DMP1-PG in cranial defect repair.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that the loss of OPN results in impaired osteoclast activity, which leads to impaired bone resorption (88). A more recent publication has outlined that mechanical stress in the sagittal cranial suture of neonatal mice leads to modified expression of OPN, suggesting that OPN is active in the osteoblast differentiation process in cranial sutures (112). Another study has suggested that BSP and OPN have a functional overlap, as they have the potential to compensate for each other's absence in response to a hormonal challenge (113).…”
Section: Craniofacial Skeletonmentioning
confidence: 99%